Polycyclic Furanobutenolide-Derived Cembranoid and Norcembranoid Natural Products: Biosynthetic Connections and Synthetic Efforts - Craig, Robert A. (Chem Rev, 2017)
The polycyclic furanobutenolide-derived cembranoid and norcembranoid natural products are a family of congested, stereochemically complex, and extensively oxygenated polycyclic diterpenes and norditerpenes. Although the elegant architectures and biological activity profiles of these natural products have captured the attention of chemists since the isolation of the first members of the family in the 1990s, the de novo synthesis of only a single polycyclic furanobutenolide-derived cembranoid and norcembranoid has been accomplished. This article will begin with a brief discussion of the proposed biosyntheses and biosynthetic connections among the polycyclic furanobutenolide-derived cembranoids and norcembranoids followed by a comprehensive review of the synthetic efforts toward each member of the natural product family, including biomimetic, semisynthetic, and de novo synthetic strategies. This body of knowledge has been gathered in order to provide insight into the reactivity and constraints of these compact and highly oxygenated polycyclic structures, as well as to offer guidance for future synthetic endeavors.